Validation of the Trauma Bonding Scale for Adults© in Kenya - Chenneville, Tiffany (Journal of interpersonal violence, 2024)
Recently validated among a sample of young adults in the United States, the Trauma Bonding Scale for Adults© is a much-needed instrument for assessing trauma bonding, which refers to the emotional attachment that often develops between perpetrators and victims of violent and exploitive crimes and is common among survivors of sex trafficking. To assess its utility with other populations, this study aimed to validate the Trauma Bonding Scale for Adults© with a sample of young adults in Kenya. An anonymous survey containing demographic items, the Trauma Bonding Scale for Adults©, and 12 items from an open-source measure of posttraumatic stress disorder was administered to 538 young adults aged 18 to 29 in Kenya using Qualtrics XM. Findings from an analysis of psychometric properties suggest that the Trauma Bonding Scale for Adults© is a valid and reliable measure of trauma bonding that may be useful in a global context.